Pharmacological mTOR inhibitors in ameliorating Alzheimer’s disease: current review and perspectives - Xie, Pei-Lun; Zheng, Meng-Yu; Han, Ran; Chen, Wei-Xin; Mao, Jin-Hua (Frontiers in Pharmacology, 2024)
Traditionally, pharmacological mammalian/mechanistic targets of rapamycin (mTOR) kinase inhibitors have been used during transplantation and tumor treatment. Emerging pre-clinical evidence from the last decade displayed the surprising effectiveness of mTOR inhibitors in ameliorating Alzheimer's Disease (AD), a common neurodegenerative disorder characterized by progressive cognitive function decline and memory loss. Research shows mTOR activation as an early event in AD development, and inhibiting mTOR may promote the resolution of many hallmarks of Alzheimer's. Aberrant protein aggregation, including amyloid-beta (Aβ) deposition and tau filaments, and cognitive defects, are reversed upon mTOR inhibition. A closer inspection of the evidence highlighted a temporal dependence and a hallmark-specific nature of such beneficial effects. Time of administration relative to disease progression, and a maintenance of a functional lysosomal system, could modulate its effectiveness. Moreover, mTOR inhibition also exerts distinct effects between neurons, glial cells, and endothelial cells. Different pharmacological properties of the inhibitors also produce different effects based on different bloodbrain barrier (BBB) entry capacities and mTOR inhibition sites. This questions the effectiveness of mTOR inhibition as a viable AD intervention strategy. In this review, we first summarize the different mTOR inhibitors available and their characteristics. We then comprehensively update and discuss the pre-clinical results of mTOR inhibition to resolve many of the hallmarks of AD. Key pathologies discussed include Aβ deposition, tauopathies, aberrant neuroinflammation, and neurovascular system breakdowns.